Bottom-up versus Top-down Campaigning at the Scottish Independence Referendum 2014 - Peter Lynch (Revue Française de Civilisation Britannique, 2015)
The Scottish independence referendum of 2014 saw one of the longest political campaigns in modern UK politics. The referendum saw the formation of a hybrid Yes campaign that combined modern campaigning techniques with a large, activist grassroots that established a range of new political organisations. Not only did these organisations continue to develop after the referendum itself, but they contributed to the formation of a broad social movement in favour of independence for the first time in Scotland.